Pembangunan aplikasi Smart al-Q dalam pembelajaran Hifz al-Quran bagi program Tahfiz Model Ulul Albab (TMUA) di sekolah menengah kebangsaan agama (SMKA) Zon Utara - Ismail, Salleh (2025)
The Tahfiz Model Ulul Albab (TMUA) programme under the Integrated Tahfiz Curriculum (KBT) requires enhancement in its technology-based learning components to ensure that Tahfiz education remains competitive and comparable with other national curricula. However, the development of technological support materials for Tahfiz education has not received sufficient attention. This study aims to develop a prototype of the Smart al-Q application as a technological support tool for Hifz al-Quran learning in TMUA secondary schools in the Northern Zone, in response to the demands of the Fourth Industrial Revolution (IR4.0) and contemporary educational needs. This study employed the Design and Development Research (DDR) methodology, which consists of three phases. The first phase involved a needs analysis using a mixed-method approach (quantitative and qualitative) to examine the necessity for developing the application. The second phase focused on the design and development of the application, utilizing the Fuzzy Delphi Method (FDM) based on the views and consensus of 15 experts. The third phase encompassed usability testing through quantitative methods to evaluate the effectiveness and practicality of the Smart al-Q application. The first phase revealed a high level of student interest in the Smart al-Q application (M = 4.53). In the second phase, Fuzzy Delphi analysis confirmed expert agreement on all constructs and items in the design and development process, with all threshold values (d) ≤ 0.2, indicating strong consensus. Defuzzification scores were used to identify the most critical items to ensure the prototype aligned with expert expectations. The third phase showed positive usability feedback, with mean scores exceeding 4.0. Inferential analysis using the Mann-Whitney U and Kruskal-Wallis tests indicated no significant differences based on school location; however, a significant gender difference was found (U=764.50, p =0.040), with female students giving higher usability ratings. The Smart al-Q application integrates modern technology with the traditional talaqqi musyafahah approach, making it a viable tool for technologyenhanced learning in Hifz al-Quran education. Theoretically, this study supports the relevance of al-Qabisi’s educational philosophy and the VARK learning model in the context of contemporary technological applications. Practically, the application facilitates Quran memorization, enables progress monitoring, and promotes more effective integration of technology within the TMUA programme across SMKA schools.